Rancangan Kegiatan Pembelajaran Berdasarkan Model Pembelajaran Time Token Untuk Meningkatkan Percaya Diri Siswa Kelas IV Sekolah Dasar - FAJAR ANISYA RAHMAYANTHI, - (2020)
ABSTRACT This research is based on student's low confidence. One of the alternative of learning model that can improve student's confidence is Time Token learning model. The purpose of the study is to design learning design based on Time Token learning model as an effort to improve student's confidence. The subject of the study is the expert in learning field. This study uses Delphi Method. The study uses survey, interview and quesioner to gather the data. The study uses qualitatif data analysis. The result of the study is learning design based on Time Token learning to improve student's confidence of fourth grade of elementary school. Keyword: Cinfidence, Time Token Learning Model, Learning Design